Combined physiological and metabolomic analysis reveals the effects of different biostimulants on maize production and reproduction - Li, Bingyan; Song, Dali; Guo, Tengfei; Xu, Xinpeng; Ai, Chao; Zhou, Wei (Frontiers in Plant Science, 2022)
Plant biostimulants (PBs) are a potential strategy to improve crop growth and grain quality. In the present study, 100 mg/L trehalose, chitosan, humic acid and gamma-aminobutyric acid treatments were applied to analyze the effects of maize production and reproductive characteristics. The contents of nitrogen, phosphorus and potassium and grain quality were significantly affected by the PBs, but not yield. The seed germination rate of all PB treatments was significantly reduced, but the drought resistance of progeny seedlings was significantly improved, with humic acid having the strongest effect. Liquid chromatography mass spectrometry analysis indicated that the disruption of the tricarboxylic acid cycle, probably due to the blockage of intermediate anabolism, reduced the supply of energy and nutrients in the early stages of germination, thus inhibiting seed germination, while the increased resistance of the offspring seedlings may be due to the up-regulation of the synthesis of unsaturated fatty acids and alkaloids by humic acid treatment. This study revealed the similarity and heterogeneity of the effects of different PBs on nutrient accumulation, yield characteristics and grain quality of maize, providing guidance for the application of PBs in intensive and sustainable agricultural production.